A simple and new fluorescent and colorimetric probe based on NBD–maleimide for detecting thiols in living cells1. Issue 15 (7th August 2015) - Shen, Youming; Liu, Chang; Zhang, Youyu; Zhang, Xiangyang; Zhang, Chunxiang; Jin, Junling; Liu, Xuewen; Li, Haitao; Yao, Shouzhuo
<x xml:space="preserve">Abstract</x> A simple and new fluorescent and colorimetric probe bearing 7-nitrobenz-2-oxa-1, 3-diazole and 4-maleimidophenol fragments for biothiols was designed and synthesized.